Heraldry in Macedonia with Special Regard to the People’s/Socialist Republic of Macedonia until 1991 - Jovan Jonovski (Genealogy, 2021)
Every European region and country has some specific heraldry. In this paper, we will consider heraldry in the People’s/Socialist Republic of Macedonia, understood by the multitude of coats of arms, and armorial knowledge and art. Due to historical, as well as geographical factors, there is only a small number of coats of arms and a developing knowledge of art, which make this paper’s aim feasible. This paper covers the earliest preserved heraldic motifs and coats of arms found in Macedonia, as well as the attributed arms in European culture and armorials of Macedonia, the кing of Macedonia, and Alexander the Great of Macedonia. It also covers the land arms of Macedonia from the so-called Illyrian Heraldry, as well as the state and municipal heraldry of P/SR Macedonia. The paper covers the development of heraldry as both a discipline and science, and the development of heraldic thought in SR Macedonia until its independence in 1991.